Implementation of Group Guidance with Group Discussion Techniques to Improve Student Interpersonal Communication - Danil Dalimunthe; Nurhayani Nurhayani (Universitas Muhammadiyah Enrekang, 2024)
Communication is an absolute necessity for human life. Communication provides something to other people with certain contacts or by using tools. A lot of communication occurs and takes place but sometimes the target of what is communicated does not reach. The aim of this research is to find out how students' interpersonal communication works. This research uses quantitative experimental methods with a one group pretest posttest design. The population in this study were all class The data analysis used was the Wilcoxon Signed Ranks Test. The results obtained from the Wilcoxon signed rank test show that it can be concluded that group guidance services are effective in improving students' interpersonal communication